Intravitreal bevacizumab versus ranibizumab for the treatment of retinal angiomatous proliferation. (22nd September 2011) - Parodi, Maurizio B.; Iacono, Pierluigi; Menchini, Francesca; Sheth, Saumil; Polini, Giovanni; Pittino, Raffaele; Bandello, Francesco
Abstract: Purpose:  To evaluate the effects of intravitreal bevacizumab and ranibizumab treatments in retinal angiomatous proliferation (RAP). Methods:  Fifty patients affected by RAP were randomly assigned either to intravitreal bevacizumab injection (IVBI) or intravitreal ranibizumab injection (IVRI). After a loading phase including three consecutive monthly injections, the retreatment was administered in cases of persistent RAP. The primary outcome measures were the mean changes in BCVA between the two treatment groups, and the proportion of eyes gaining 1 and 3 lines at the end of the follow‐up. Secondary outcomes included central macular thickness (CMT) changes and progression to more advanced stages of RAP. Results:  Fifty patients affected by stage 1 and 2 RAP were recruited. Twenty‐six and 24 patients received IVBI and IVRI, respectively. At the baseline, mean best corrected visual acuity (BCVA) values were 0.59 ± 0.21 (LogMAR ± SD, approximately corresponding to 20/80 Snellen Equivalent‐SE) in IVBI group and 0.66 ± 0.33 (approximately 20/90 SE) in IVRI group with no statistical difference. At 12‐month examination, both groups showed a statistically significant improvement in the BCVA, with a final mean value of 0.43 ± 0.24 (approximately 20/54 SE) in IVBI group and 0.50 ± 0.32 (approximately 20/63 SE) in the IVRI group. A BCVA gain of 1 and 3 lines was registered in 20 and 8 eyes, respectively, in the IVBI group. Similarly, 17 and 7 eyes showed an improvement of 1 or 3 lines, respectively, in the IVRI group. The CMT reduced significantly from baseline to 12‐month examination in both groups. A lower proportion of eyes with complete pigment epithelium detachment resolution was noted in the IVBI group than in the IVRI group (40% versus 90%). Conclusions:  Our study shows that both IVBI and IVRI are equally effective in improving the BCVA over a 1‐year follow‐up in eyes affected by stage 1 and 2 RAP.